EMPOWERMENT OF PALM SUGAR PROCESSING COMMUNITIES: AN EFFORT TO INCREASE ADDED VALUE THROUGH EXTENSION ON PALM SUGAR CROP DIVERSIFICATION IN POLINGGONA DISTRICT, POLINGGONA DISTRICT, KOLAKA REGENCY - Jumi , Jumi; Halima, Natalia; Agustin, Giska Nuraeni; Ahmad, Ahmad; Purbaningsih, Yuli (International Journal of Engagement and Empowerment (IJE2), 2026)
The community empowerment program was conducted in Polinggona Village, Polinggona District, Kolaka Regency, which has considerable potential in aren palm (Arenga pinnata) resources. However, the utilization of aren palm remains limited due to traditional processing practices, limited production technology, low product diversification, inadequate packaging and marketing, and low added value. This program aimed to improve the knowledge and skills of aren palm processors through counseling, training, and participatory assistance in developing diversified aren-based products. The activity used a participatory approach through field observation, Focus Group Discussion (FGD), problem identification, counseling, appropriate technology introduction, and hands-on practice of product diversification. The results showed that the activities provided participants with knowledge and practical skills related to aren palm cultivation, hygienic processing, the use of appropriate production technology, product diversification, packaging, and digital marketing. The diversification practice resulted in aren chips as an alternative processed product with potential to increase product variety and economic value. The program also encouraged participants to improve product packaging and develop wider marketing opportunities. Overall, the activities contributed to strengthening the capacity of the partner community in processing aren palm products and supporting the development of local economic potential in a more sustainable manner.